Burnout rate and related factors among midwives who work in sanandaj - Hana Sohrabi; Shaghayegh Majzobi; Ronak Shahoei (Kurdistan University of Medical Sciences, 2018)
Background & Aim: Job burnout is defined as the response to the chronic psychological distress caused by one’s occupation, leading to poor efficiency and loss of human resources. The present study aimed to evaluate the rate of job burnout and its influential factors in the midwives employed at the hospitals and health centers in Sanandaj, Iran in 2016. Materials and Methods: This descriptive-analytical study was conducted on 200 midwives employed at the hospitals and health centers in Sanandaj city. The subjects were selected via simple random sampling using a random number table. Data were collected using Maslach burnout inventory. Data analysis was performed in SPSS version 18 using descriptive and inferential statistics at the significance level of 0.05. Results: In terms of job burnout dimensions, low cynicism was observed in 62 subjects (31%), moderate cynicism was observed in 72 subjects (36%), and severe cynicism was observed in 66 subjects (33%). Low emotional exhaustion was detected in 70 subjects (35%), moderate emotional exhaustion was observed in 74 subjects (37%), and severe exhaustion was reported in 56 subjects (28%). With regard to personal efficiency, high self-effectiveness was denoted in 71 subjects (35.5%), while the level was moderate and low in 78 (39%) and 51 subjects (25.5%). Conclusion: According to the results, the rate of job burnout was moderate among the studied midwives. Given the importance of midwifery in health care, preventive programs are recommended in order to promote the quality of care services and satisfaction of healthcare professionals, as well as reducing the rate of job burnout.